Analisis Risiko Keselamatan dan Kesehatan Kerja (K3) Menggunakan Metode HIRADC di Area Produksi Departemen Welding PT ZX - Feriyansah Feriyansah; MD. Rafifallah; Rafli Alfariz Hadiansyah; Triana Ambarwati; Yudi Prastyo (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Occupational Health and Safety (OHS) is an important aspect in the automotive manufacturing industry which has high hazard potential, especially in the welding production field. This research aims to identify potential hazards, conduct risk assessments, and determine control measures using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method at the Welding Department of PT Otomotif ZX. The research method used is descriptive quantitative through direct observation and HIRADC data analysis. The results show that out of a total of 5 main work activities, 24 potential hazards were found with risk classifications as follows: 1 extreme risk, 14 high risks, and 9 medium risks. The potential hazards include risks of cuts, burns, hearing impairment, and muscle injuries due to non-ergonomic work postures. Based on the risk assessment results, control recommendations were developed through the five levels of the hierarchy of controls, namely elimination, substitution, engineering controls, administration, and the use of personal protective equipment (PPE). The implementation of the HIRADC method has been proven effective in helping companies identify risks and determine appropriate preventive actions to create a safer and more productive work environment.